Peran Orang Tua dengan Perilaku Pencegahan Kehamilan Usia Dini pada Siswi - Merfina Alexsandra Scolastica Rori; Zainar Kasim; Silvia Dewi Mayasari Riu (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Early pregnancy is at high risk for health complications such as anemia, preeclampsia, and premature birth.In addition, social impacts such as dropping out of school, societal stigma, and economic instability also become serious consequences that can affect the future of adolescents.The objective of this study is to determine the relationship between parental roles and the prevention of early pregnancy among students at SMA Negeri 1 Touluaan.The research uses a cross-sectional design.The sample in this study consisted of 38 respondents using purposive sampling technique.Data collection on parental roles and prevention of early pregnancy was conducted using a questionnaire, analyzed using the chi-square statistical test.The results of the study on the role of parents mostly showed that the role of parents in the good category amounted to 32 respondents (66.7%), and the behavior of pregnancy prevention mostly in the good category amounted to 34 respondents (70.8%).The results of the chi-square test obtained a p-value of 0.006 where < α 0.05.Conclusion: There is a relationship between the role of parents and the prevention of early pregnancy among students of SMA Negeri 1 Touluaan.